PATH OF NATIONALISM IN THE FORMATION OF MALAYSIAN POLITICS - Ku Hasnan Ku Halim; Shuhairimi Abdullah; Ahmad Mujahid Ahmad Zaidi (Journal of Human Development and Communication (JoHDeC), 2025)
The concept of nationalism is said to have existed in the 12th century, however, this ideology only emerged as an influential political ideology in the 19th century when some colonies began to demand independence from the colonialists. Scholars of western political thought consider the year 1648 to be the turning point for the presence of nationalism as a political ideology. This was evidenced in that year by an agreement that brought an end to the 30 -year war in Europe which had implications for the birth of the nation -state concept. The treaty was the Treaty of Westphalia, in which the treaty did not affect the rights of a nation-state, and national sovereignty (Baradat; 1984). This survey study was conducted to examine the journey of nationalists in Malaysia as well as the conflicts that occurred in the formation of Malaysians through several previous studies. The results of this study can be used as a reference to determine the best concept to discuss the aspects of nationalism in Malaysia.